2013
DOI: 10.1186/1471-2474-14-184
|View full text |Cite
|
Sign up to set email alerts
|

Association of back pain with hypovitaminosis D in postmenopausal women with low bone mass

Abstract: Background: Back pain is a major public health problem due to its high frequency, to the resulting activity constraint, and the need for surgery in many cases. Back pain is more frequent in women than men, mainly in postmenopausal women. High prevalence of hypovitaminosis D has been detected in postmenopausal women, and it is associated with decreased bone mass, sarcopenia, vertebral fractures, and inflammation, which can be related to back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
1
22
0
2
Order By: Relevance
“…In study conducted by. These in agreement with studies reported an association between vitamin D deficiency and LBP (30,31) . However a few studies have found no association between vitamin D deficiency and musculoskeletal pain (32,33) .…”
Section: Discussionsupporting
confidence: 82%
“…In study conducted by. These in agreement with studies reported an association between vitamin D deficiency and LBP (30,31) . However a few studies have found no association between vitamin D deficiency and musculoskeletal pain (32,33) .…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in accordance with the earlier results of Lodh et al [12] in which the patients (women were the vast majority) with back pain had a significantly lower concentration of vitamin D, compared to healthy volunteers. In a study of Brazilian postmenopausal women, the majority of women with vitamin D deficiency did not experience any back pain (69.5 vs. 66.9%), greater limitation of daily activities, nor any fractures when compared to the women without D hypovitaminosis D [10].…”
Section: Discussionmentioning
confidence: 92%
“…Previously, vitamin D deficiency was suggested to be related with all these disorders. Vitamin D also shows anti-inflammatory properties, which can be lost when its level decreases and, in turn, musculoskeletal pain may occur [9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a multi-faceted disease and is influenced by different confounding variables. For example, depression and high BMI (Odds increases the risk of chronic low back pain [9][10][11][12][13]. Correlation between traits of anxiety and pain is both significant and positive [7].…”
Section: Discussionmentioning
confidence: 99%
“…The subjective analyses of pain were based on the VAS scale and the objective analyses of pain were done through pain score through the Pain Detect Tool [2]. The Generalized Anxiety Disorder or GAD was detected with the GAD-7 tool [6][7][8][9][10][11]. The clinical data that were surveyed include medication history of the patients through prescription transcripts.…”
Section: Methodsmentioning
confidence: 99%